Effect of vibration stimulation on dysbasia of spastic paraplegia in neuromyelitis optica: a possible example of neuronal plasticity. (8th October 2012) - Lin, Hsin-Ni; Nagaoka, Masanori; Hayashi, Yasuko; Hatori, Kozo
Abstract : We analysed the effect of vibration stimulation (VS) on dysbasia of neuromyelitis optica (NMO). The patient was a 36-year-old woman who was diagnosed with NMO and had difficulties in walking. VS was applied to the lower limb muscles on the left, more spastic, side with an ordinary vibrator. The performance of standing up and walking improved with VS. Even with improved performance after VS, the amount of surface EMG of the lower limbs did not increase as a whole, but the EMG patterns among the lower leg muscles changed remarkably. VS produced reciprocity within antagonistic muscles. Variability of EMG amplitudes decreased remarkably during the walking cycle, not only on the vibrated side, but also on the non-vibrated side. The effect lasted longer than several dozen minutes after the cessation of VS. We conjectured that central pattern generator (CPG) and neuronal plasticity were the result of VS.